Sell-Side Financial Analysts and the CFA® Program. Issue 2 (1st April 2018) - Kang, Qiang; Li, Xi; Su, Tie
Abstract : We examine the effects the Chartered Financial Analyst ® (CFA) designation program has on recommendation performance and career outcomes of the analysts who complete the CFA Program and become CFA charterholders. For these analysts, both their recommendation performance and their chances of making Institutional Investor 's All-America Research Team increased during the 1993–2015 period. These effects are attributable to the CFA Program curriculum. The results remain largely stable over the pre- and post-2000 subperiods, and they survive an array of robustness checks. Abstract : Disclosure: The authors report no conflicts of interest. Editor's Note Submitted 21 November 2015 Accepted 19 September 2017 by Stephen J. Brown